Preparation of Light Fuel Fractions from Heavy Vacuum Gas Oil by Thermal Cracking Reaction - Obyed, Saleem Mohammed (Al-Khwarizmi Engineering Journal, 2017)
This work deals with thermal cracking of heavy vacuum gas oil which produced from the top of vacuum distillation unit at Al- DURA refinery, by continuous process. An experimental laboratory plant scale was constructed in laboratories of chemical engineering department, Al-Nahrain University and Baghdad University. The thermal cracking process was carried out at temperature ranges between 460-560oC and atmospheric pressure with liquid hourly space velocity (LHSV) equal to 15hr-1.The liquid product from thermal cracking unit was distilled by atmospheric distillation device according to ASTM D-86 in order to achieve two fractions, below 220oC as a gasoline fraction and above 220oC as light cycle oil (LCO).The first fraction which was below 220oC was fractionated to light fractions (gasoline, kerosene and gas oil) by atmospheric distillation device. The fractions (gasoline, kerosene and gas oil) were distilled by atmospheric distillation device in order to obtained distillation curve for these fractions. Physical properties were recorded for these cuts to compare it with standard property test, in order to studying the possibilities of industrial uses. The maximum conversion of heavy vacuum gas oil was obtained by this process equal to 82 wt. % of feed at 540oC.